International Regimes of International Environmental Governance: Statement of the Problem - Mohammad Sarvar Anvar (Московский журнал международного права, 2015)
The necessity of formation of Inter-native modes of international environmental governance in the absence of a single, global environmental policy and environmental improvements despite conclusion of new international environmental treaties and agreements is argued. The author’s definition of an international regime of international environmental governance as a combination of international institutions, customary norms and principles, as well as formal resolutions and treaties prescribing actions the State shall in respect of a particular subject or problem in the region is suggested. It is proved that if the management of natural resources has gained some international experience, in relation to international environmental issues management is more complex due to scientific uncertainty, complex environmental degradation, and the difficulties of adoption and implementation of international obligations of States on their territory and hard harmonization with other states.